PEMASANGAN LAMPU TAMAN MENGGUNAKAN SOLAR CELL SEBAGAI SUMBER ENERGI ALTERNARIF DI KELURAHAN BENDUNG KOTA SERANG - Irlan, Ade Okvianti; Herlina, Liana; Hermawan, Fahmy; Kurniyaningrum, Endah; Rizkina, Salwa Zahra; Herprioningrum, Maharani (Universitas Trisakti, 2024)
Solar cell are a technology that converts sunlight into electrical energy. Solar energy can produce up to 156.486 MW of power, a langer amount when compared to other renewable energy sources. Indonesia is a country located in the equatorial route, which receives sufficient amount of sunlight throughout the year, with an average eye-day radiation intensity of about 4.8 kWh/m2 per day throughout Indonesia. Especially in the Jakarta area, the DKI Provincial Government had released the Governor’s Instruction (InGub) Number 66 of 2019 on air quality control, one of the points of the InGub is the installation of PLTS to minimize air pollution in Jakarta. The Jakarta Provincial Government will instal solar panels in local government buildings, school buildings, sports halls and health facilities. DKI Education Agency Head Ratiyono said that there are now 100 schools that have installed solar panels. The method used is a presentation using a power point on how to apply solar panels so that the material can reach participants using attractive visuals and direct practice. By continuing the program of DKI Provincial Government, therefore, as academicians we try to provide understanding, socialization and piloting PLTS in Serang enviroment, Banten. The pilot was implemented for garden lights in Kelurahan Bendung, this was because the field in Kelurahan Bendung was large and had minimal lighting.